Model Pelopor: Transformasi Pembelajaran Soal Cerita Matematika - Danisfa, Anggita Rose Aprilia; Suriansyah, Ahmad; Purwanti, Ratna (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study was initiated due to the low level of student participation in mathematics lessons, along with underdeveloped critical thinking and problem-solving skills, which should be key focuses in the learning process. These challenges emerged as a result of using monotonous instructional models that did not support active student engagement. As an innovative solution, this research implemented the PELOPOR learning model integrated with KOMET (Mathematics Comic) video media to create a more engaging learning environment capable of stimulating higher-order thinking skills. The classroom action research was conducted over four sessions using both qualitative and quantitative approaches. The results revealed significant improvements in each cycle. Students demonstrated highly active participation, and their critical thinking and problem-solving abilities improved to a level categorized as highly proficient. These findings emphasize that the PELOPOR model, supported by KOMET video media, is effective in transforming mathematics instruction into a more interactive and meaningful learning experience.